Analyzing the Impact of Foreign Income on Local Currency Exchange Rates: A Comprehensive Study of Dynamics and Implications - Islahiyah, Nazwa Aihan (Institute for Law and Economics Studies, 2024)
This research investigates the impact of foreign income on local currency exchange rates, emphasizing the complex dynamics between various components of foreign income including remittances, foreign direct investment (FDI), and export revenues and currency behavior. Employing a mixed-methods approach, the study combines quantitative analysis using econometric models with qualitative insights derived from expert interviews and case studies across different countries. The findings reveal a significant positive correlation between foreign income inflows and local currency appreciation, particularly in developing and emerging economies. However, the study also highlights potential inflationary pressures resulting from increased foreign income, suggesting that policymakers must carefully manage these dynamics through proactive monetary policies and fiscal strategies. Furthermore, the research underscores the importance of understanding currency risk for investors, particularly in emerging markets where foreign income plays a pivotal role in shaping economic stability. Overall, this study contributes to the existing literature by elucidating the multifaceted relationship between foreign income and exchange rates, providing critical implications for policymakers and investors in a globalized economy.